2022
DOI: 10.1101/2022.02.24.481622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A central protein complex essential for Invasion inToxoplasma gondii

Abstract: Apicomplexa are obligate intracellular parasites. While most species are restricted to specific hosts and cell types, Toxoplasma gondii can invade every nucleated cell derived from warm-blooded animals. This broad host range suggests that this parasite can recognize multiple host cell ligands or structures, leading to the activation of a central protein complex, which should be conserved in all apicomplexans. During invasion, the unique secretory organelles (micronemes and rhoptries) are sequentially released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…However, CRMPs behavior strongly argues for a function specifically at the time of rhoptry exocytosis. CRMPs and their partners Tg247195 and Tg277910 seem to not be part of the previously described Nd/NdP exocytic complex, also confirmed by a parallel study (preprint: Singer et al , 2022). However, we cannot exclude the existence of a dynamic/transient complex formed by CRMPs and Nd proteins at the time of rhoptry exocytosis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, CRMPs behavior strongly argues for a function specifically at the time of rhoptry exocytosis. CRMPs and their partners Tg247195 and Tg277910 seem to not be part of the previously described Nd/NdP exocytic complex, also confirmed by a parallel study (preprint: Singer et al , 2022). However, we cannot exclude the existence of a dynamic/transient complex formed by CRMPs and Nd proteins at the time of rhoptry exocytosis.…”
Section: Discussionsupporting
confidence: 70%
“…Tg277910 and Tg247195 possess one and three thrombospondin type 1 (TSP‐1) domains, respectively (Fig 3C), known to participate in cell adhesion (Adams & Tucker, 2000). In addition, Tg247195 possesses an H‐type lectin domain (Pietrzyk‐Brzezinska & Bujacz, 2020) and, interestingly, has a role in invasion (preprint: Singer et al , 2022; Possenti et al , 2022) and rhoptry secretion (Possenti et al , 2022). To determine the function of Tg277910, we generated an inducible knockdown HA 3 ‐tagged line (Tg277910_iKD; Fig EV3E–G).…”
Section: Resultsmentioning
confidence: 99%
“…The non-micronemal localization of RDF1 and RDF2 shown in the present work is further supported by spatial hyperLOPIT (Localization of Organelle Proteins by Isotopic Tagging) data ( Barylyuk et al, 2020 ), which demonstrated that RDF1 is part of a separate minicluster including another member of the thrombospondin family (TGME49_277910) and two multipass TM proteins (TGGT1_261080, TGGT1_292020) showing homology to the Plasmodium Cysteine-Repeat Modular Proteins ( Thompson et al, 2007 ; Douradinha et al, 2011 ). Interestingly, two recent studies deposited in a preprint repository ( Singer et al, 2022 ; Sparvoli et al, 2022 ) showed that TGGT1_261080 and TGGT1_292020 depletion impairs rhoptry discharge and that these two molecules are part of a multiprotein complex also including RDF1. These results support a model in which RDF1 and RDF2 play a key role as Coccidia-specific components of a protein complex acting as a sensor of parasite-host cell contact leading to rhoptry exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The non micronemal localization of RDF1 and RDF2 shown in the present work is further supported by spatial hyperLOPIT (Localisation of Organelle Proteins by Isotopic Tagging) data (Barylyuk et al, 2020), which demonstrated that RDF1 is part of a separate minicluster including another member of the thrombospondin family (TGME49_277910) and two multipass TM proteins (TGGT1_261080, TGGT1_292020) showing homology to the Plasmodium Cysteine-Repeat Modular Proteins (Douradinha et al, 2011; Thompson et al, 2007). Interestingly, two recent studies deposited in a preprint repository (Singer et al, 2022; Sparvoli et al, 2022) showed that TGGT1_261080 and TGGT1_292020 depletion impairs rhoptry discharge and that these two molecules are part of a multiprotein complex also including RDF1. These results support a model in which RDF1 and RDF2 play a key role as Coccidia-specific components of a protein complex acting as a sensor of parasite-host cell contact leading to rhoptry exocytosis.…”
Section: Discussionmentioning
confidence: 99%